Therapeutic effects of stem cell–derived extracellular vesicles in animal models of intervertebral disc degeneration: a systematic review and meta-analysis of species differences and delivery strategies - Wei, Yi-Ping; Shiue, Yow-Ling; Tsai, Chun-Sheng; Tarng, Yih-Wen (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectivesIntervertebral disc degeneration (IVDD) is a major contributor to chronic low back pain and disability worldwide, yet current treatments remain largely palliative and do not restore disc structure or biomechanical integrity. Stem cell–derived extracellular vesicles (SC-sEVs) have emerged as promising cell-free biologics capable of modulating inflammation, apoptosis, and extracellular matrix homeostasis.MethodsThis systematic review and meta-analysis evaluated the therapeutic efficacy of SC-sEVs in rat models of puncture-induced IVDD, with a specific focus on comparing hydrogel-assisted versus direct (non-hydrogel) delivery strategies. The review was prospectively registered in PROSPERO (CRD420250654980) and conducted according to PRISMA 2020 guidelines.ResultsComprehensive searches of PubMed, Embase, and the Cochrane Library through August 2025 identified 19 studies enrolling 305 rats. Extracted outcomes included disc height index (DHI), MRI Pfirrmann grade, and histological score. Meta-analysis demonstrated significant improvements in DHI (mean difference [MD] = 12.8%, 95% CI 7.6–18.0), histological grade (MD = −4.1, 95% CI –5.1 to −3.2), and MRI Pfirrmann grade (MD = −1.5, 95% CI –1.8 to −1.2) at 4–8 weeks following treatment. Hydrogel-assisted delivery produced comparable overall efficacy to direct injection but contributed to reduced interstudy heterogeneity. Both human- and rat-derived EVs significantly improved all evaluated outcomes, with human-source EVs showing a modest advantage in MRI grading (P = 0.017). Risk-of-bias assessment indicated generally acceptable methodological quality, and no substantial publication bias was observed.ConclusionOverall, SC-sEV therapy demonstrates consistent regenerative benefits in preclinical IVDD models, supporting its translational promise as a minimally immunogenic, cell-free therapeutic for degenerative spine disorders. Future studies employing standardized protocols, mechanistic analyses, and long-term evaluation are needed to facilitate clinical translation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250654980, identifier CRD420250654980.